Long-term Surgical Outcome of Congenital Pseudarthrosis of the Tibia - Ong TJ; Jamil K; Abd-Rasid AF; Abdul-Rashid AH; Ibrahim S (Malaysian Orthopaedic Journal)
Introduction: Congenital pseudarthrosis of the tibia (CPT) is challenging to treat. The main issues following surgery are non-union, refracture, limb deformity and length discrepancy. We evaluated the surgical outcome of children operated in our centre. Materials and methods: A retrospective study of the outcome of primary bone union, refracture and success rate. Patients who had reached skeletal maturity were further evaluated for Johnston grading, residual limb deformity and limb length discrepancy (LLD). Results: Twelve patients (13 tibiae) were reviewed with an average follow-up of 14.5 years (range 3.1-24.0 years). Nine (69.2%) tibiae underwent intramedullary (IM) rodding; two (15.4%) were stabilised with the Ilizarov external fixator (IEF) + IM rod; and two other (15.4%) tibiae with the IEF only. Primary union was achieved in 5 (38.5%) tibiae, but refractures occurred in two tibiae (40%), lowering the overall success rate to 23.1%. Fixation with IM rodding alone led to a low primary union rate (22.2%) but combining it with IEF avoided refracture. Seven (53.8%) tibiae reached skeletal maturity and had a union at 12.6 years (7.5–17.4 years), after an average of 3 surgical procedures. Four (57.1%) were Johnston Grade I, and 3 (42.9%) were Grade II. Four (57.1%) tibiae had residual tibial valgus, two (28.6%) tibial varus, four (57.1%) procurvatum and one (14.3%) recurvatum. The average LLD was 3.9cm (2-10cm). Conclusion: Intramedullary rodding alone is ineffective for producing a bony union but combining it with IEF minimise the refracture rate. The chances of union increased with age, but residual deformity and shortening are an ongoing challenge.